2011
DOI: 10.1007/s11240-011-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple shoot induction and plant regeneration of the single-cell C4 species Bienertia sinuspersici

Abstract: Direct organogenesis provides an efficient means of propagating plants in vitro without the necessity of growing callus cultures. Shoot regeneration was achieved from bud explants of Bienertia sinuspersici on Murashige and Skoog's media supplemented with 6-benzyladenine (BA). The frequency of regeneration varied based on the concentration of BA used. The highest rate of new shoot induction was observed when explants were cultured on media containing 4.4 lM BA after three weeks. Shoots were successfully elongat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Except for two reports on the regeneration using indirect organogenesis as well as direct shoot micropropagation [11] [12], no additional in vitro studies on the rapid vegetative propagation of B. sinuspersici have been documented. The purpose of this study is to examine the effects of Murashige and Skoog (MS) basal medium strengths and various auxins on the induction of adventitious roots in B. sinuspersici cuttings so that an efficient and rapid method for vegetative propagation of massive plant material can be established.…”
Section: Introductionmentioning
confidence: 99%
“…Except for two reports on the regeneration using indirect organogenesis as well as direct shoot micropropagation [11] [12], no additional in vitro studies on the rapid vegetative propagation of B. sinuspersici have been documented. The purpose of this study is to examine the effects of Murashige and Skoog (MS) basal medium strengths and various auxins on the induction of adventitious roots in B. sinuspersici cuttings so that an efficient and rapid method for vegetative propagation of massive plant material can be established.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with Byrne and Caponetti (1992), who reported that 2,4-D and sucrose were necessary to produce calli in the Boston fern, Nephrolepis exaltata . Calli are very sensitive to in vitro culture conditions and easily turn brown (Ahloowalia, 1982; Northmore et al, 2012). It has been reported to be difficult for generating intact sporophytes from a callus in ferns (Kwa et al, 1997; Byrne and Caponetti, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies are available for discovering the true nature of somaclonal variation, including phenotypic identification (Kong et al, 2011), cytological analysis (Konieczny et al, 2010), DNA analysis techniques (Torres Morán et al, 2010;Ai et al, 2011), and protein analysis (Northmore et al, 2012). In recent years, DNAbased molecular markers have served as a significant tool for evaluating heritable homogeneity and the trueto-type nature of in vitro propagated plants.…”
mentioning
confidence: 99%